The Arab Spring - Nazar Ul Islam Wani (International Institute of Islamic Thought, 2019)
The Arab Spring was a series of protests which took place in Arab countries against longstanding dictatorial regimes, because of the latter’s inability or refusal to deliver socio-economic and political justice to the common 99 masses. Protests spread like fire and made an impact not only on the governance of the Arab world but also internationally, by involving big players like Russia and the United States of America. Yet these events were intensely complicated, with multiple actors and layers of history involved in each country. The book under review here is one prodigious effort to understand the Arab Spring, considering causes and effects of the uprisings. Structurally, the book is divided into two parts. The first part, consisting of seven chapters, deals with the uprisings in Arab countries; part two, consisting of six chapters, discusses the impact of the Arab Spring on the non-Arab world and their core interests related to the uprisings.